Genetic Engineering of Streptomyces natalensis VTCC-A-3245 to Improve Its Natamycin Production - Oanh, Nguyễn Thị Hà; Vân, Nguyễn Thị; Thảo, Nguyễn Kim Nữ (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: Natamycin, a polyene compound with broad-spectrum activity against yeasts and fungi, was firstly found in Streptomyces natalensis . Because of its low toxicity to mammalian cells, natamycin is widely used in food industry and medicine to prevent fungal growth. Although natamycin has been used worldwide, this antifungal compound has not been produced in Vietnam. One of the reasons is that we do not own any industrial-scale production strain. In order to develop such production strain, strain improvement must be involved. Therefore, we carried out the study “Genetic engineering of Streptomyces natalensis VTCC-A-3245 to improve its production of natamycin”. In this study, we introduced a copy of the gene pimM , a positive regulator gene in the natamycin biosynthetic pathway, into S. natalensis chromosome, hence boosting the expression of the structural genes, resulting in the increase of natamycin production. As a result, a recombinant pSET152 plasmid containing pimM was constructed and transformed successfully into E. coli ET12567. After conjugation, a S. natalensis mutant carrying an additional copy of pimM was obtained. The result showed that the level of natamycin produced by the S. natalensis mutant strain increased 3 fold compared to the S. natalensis wildtype strain. Keywords: Streptomyces natalensis, natamycin, strain improvement, pimM.